Severe upper airway obstruction due to delayed retropharyngeal hematoma formation following blunt cervical trauma - Ciceri David P (BMC Anesthesiology, 2007)
Abstract Background We report a case of severe upper airway obstruction due to a retropharyngeal hematoma that presented nearly one day after a precipitating traumatic injury. Retropharyngeal hematomas are rare, but may cause life-threatening airway compromise. Case presentation A 50 year-old man developed severe dyspnea with oropharyngeal airway compression due to retropharyngeal hematoma 20 hours after presenting to the emergency department. The patient also had a fractured first cervical vertebra and was diagnosed with a left brachial plexopathy. The patient underwent emergent awake fiberoptic endotracheal intubation to provide a definitive airway. Conclusion Retropharyngeal hematoma with life-threatening airway compromise can develop hours or days after a precipitating injury. Clinicians should be alert to the potential for this delayed airway collapse, and should also be prepared to rapidly secure the airway in this patient population likely to have concomitant cervical spinal or head injuries.